Assessing the impact of posture on diaphragm morphology and function using an open upright MRI system—A pilot study. Issue 130 (September 2020) - Safavi, Shahideh; Arthofer, Christoph; Cooper, Andrew; Harkin, James W.; Prayle, Andrew P.; Sovani, Milind P.; Bolton, Charlotte E.; Gowland, Penny A.; Hall, Ian P.
Highlights: Subjects tolerated scanning in an open-configuration upright MRI system. The greatest change diaphragm morphology with breathing was seen in the healthy. This MRI facilitates the assessment of diaphragm in those with diaphragm disease. Abstract: Purpose: The diaphragm is the most important muscle of respiration. Disorders of the diaphragm can have a deleterious impact on respiratory function. We aimed to evaluate the use of an open-configuration upright low-field MRI system to assess diaphragm morphology and function in patients with bilateral diaphragm weakness (BDW) and chronic obstructive pulmonary disease (COPD) with hyperinflation. Method: The study was approved by the National Research Ethics Committee, and written consent was obtained. We recruited 20 healthy adult volunteers, six subjects with BDW, and five subjects with COPD with hyperinflation. We measured their vital capacity in the upright and supine position, after which they were scanned on the 0.5 T MRI system during 10-s breath-holds at end-expiration and end-inspiration in both positions. We developed and applied image analysis methods to measure the volume under the dome, maximum excursion of hemidiaphragms, and anterior-posterior and left-right extension of the diaphragm. Results: All participants were able to complete the scanning protocol. The patients found scanning in the upright position more comfortable than the supine position. All differences in the supine inspiratory-expiratory parameters, excluding left-right extension, were significantly smaller in the BDW and COPD groups compared with healthy volunteers. No significant correlation was found between the postural change in diaphragm morphology and vital capacity in either group. Conclusion: Our combined upright-supine MR imaging approach facilitates the assessment of the impact of posture on diaphragm morphology and function in patients with BDW and those with COPD with hyperinflation.